2023
DOI: 10.1038/s41467-023-36534-9
|View full text |Cite
|
Sign up to set email alerts
|

Ozone exposure disrupts insect sexual communication

Abstract: Insect sexual communication often relies upon sex pheromones. Most insect pheromones, however, contain carbon-carbon double bonds and potentially degrade by oxidation. Here, we show that frequently reported increased levels of Anthropocenic ozone can oxidize all described male-specific pheromones of Drosophila melanogaster, resulting in reduced amounts of pheromones such as cis-Vaccenyl Acetate and (Z)−7-Tricosene. At the same time female acceptance of ozone-exposed males is significantly delayed. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This shift in reproductive behaviour is consistent with established knowledge that eO 3 can disrupt insect pheromonal communication through oxidative stress and the breakdown of pheromone compounds (Li‐Byarlay et al., 2016; Tasaki et al., 2017). Our findings are further supported by previous research, which emphasized the harmful impact of eO 3 on pheromonal communication (Arndt, 1995; Jiang et al., 2023; Vanderplanck et al., 2021). This disruption has implications for the population dynamics and interactions of MPB, illustrating the profound effects that eO 3 can have on insect behaviour and reproduction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This shift in reproductive behaviour is consistent with established knowledge that eO 3 can disrupt insect pheromonal communication through oxidative stress and the breakdown of pheromone compounds (Li‐Byarlay et al., 2016; Tasaki et al., 2017). Our findings are further supported by previous research, which emphasized the harmful impact of eO 3 on pheromonal communication (Arndt, 1995; Jiang et al., 2023; Vanderplanck et al., 2021). This disruption has implications for the population dynamics and interactions of MPB, illustrating the profound effects that eO 3 can have on insect behaviour and reproduction.…”
Section: Discussionsupporting
confidence: 92%
“…The CO 2 generator was connected to a liquefied petroleum gas tank outside the tent. The second tent with an O 3 generator (the DC PRO 450 Ozone Generator, Langley, BC, Canada) and a controller (EcoZone™ Model EZ‐1X, Newark, CA, USA) equipped with a timer, maintained 100 ppb of O 3 (eO 3 ) (Jiang et al., 2023; Masui et al., 2023; Pinto et al., 2007). The third tent was the control under ambient conditions (mean ± SE; CO 2 = 485.14 ± 8.74, O 3 = 18.58 ± 0.59).…”
Section: Methodsmentioning
confidence: 99%
“…Atmospheric changes may also affect pheromone communication in different ways. First, reported levels of increases in oxidative greenhouse gases, like ozone, have been shown to alter the chemical structure of pheromones through oxidation, thereby interfering with communication ( 122 124 ). Second, increasing ambient temperatures have been shown to significantly increase pheromone decay and, therefore, pheromone following by recruits in ants ( 125 ).…”
Section: Anthropogenic Change and Communicationmentioning
confidence: 99%
“…For example, (Z)-7-tricosene acts as a sex chemical stimulant in Drosophila melanogaster (Grillet et al, 2006), and when present together with (Z)-7-pentacosene, both occur in different relative amounts when the fruit flies are exposed to ozone (Jiang et al, 2023). Furthermore, (Z)-7-heptacosene and (Z)-7-nanocosene seem to act as sex pheromones in wood wasps (Böröczky et al, 2009).…”
Section: Chemical Profile Of Femalesmentioning
confidence: 99%
“…Moreover, environmental stressors, such as changes in temperature, drought, and ozone, have been found to impact insect reproduction. These stressors have been found to change the time needed for finding a partner, to alter courtship displays and mating duration, and to disrupt sex recognition (Candolin et al, 2007;Gefen & Gibbs, 2009;Conrad et al, 2017;Jiang et al, 2023). Given the ongoing environmental disturbance in agricultural fields with increased landscape alteration and use of pesticides, populations of solitary bees, which are among the most important group of pollinators worldwide (Klein et al, 2007;Giannini et al, 2015), have been demonstrated to be in decline (Potts et al, 2010;Raven & Wagner, 2021).…”
Section: Introductionmentioning
confidence: 99%